Postoperative atrial arrhythmias after bilateral lung transplantation with intraoperative V-A extracorporeal membrane oxygenation: a single-center experience - Boscolo, Annalisa; Sella, Nicolò; Zarantonello, Francesco; Pittorru, Raimondo; Mormando, Giulia; Bertoncello, Carlo Alberto; Curmaci, Elena; Ceccato, Roberta; Fincati, Valentina; Masetti Zannini, Paola; Bianco, Angela; Coniglio, Giordana; et al. (Frontiers in Transplantation, 2025)
IntroductionLung transplantation (LT) is the standard treatment for end-stage chronic respiratory failure that does not respond to other therapies. Advances in surgical techniques and perioperative care have improved survival rates. However, postoperative complications, particularly atrial arrhythmias (AA) remain clinically significant. Although AAs are frequently observed in the early postoperative period, data regarding their incidence and impact on outcomes are scarce. This observational study aims to: (i) assess the incidence of new-onset postoperative AA within one month of bilateral LT; (ii) evaluate their impact on short- and mid-term outcomes; and iii) identify potential predictors.Materials and methodsWe retrospectively reviewed all consecutive bilateral LT recipients admitted to the Intensive Care Unit (ICU) of the University Hospital of Padua between October 2021 and December 2023. Clinical variables, perioperative right heart catheterization data, and echocardiographic measurements were collected.ResultsA total of 85 LT recipients were enrolled. Postoperative AA occurred in 27 patients (32%), with atrial fibrillation emerging as the most common arrhythmia (55.6%). The remaining 58 (68%) patients did not develop any arrhythmic disorder. Many AA patients (22, 81.5%) required treatment with antiarrhythmic drugs or electrical cardioversion. Compared to the control group, AA patients were older (p-value 0.002) and usually affected by coronary heart disease (18.5% vs. 5.2%, p-value 0.05) and obstructive respiratory disease (55.5% vs. 27.7%, p-value 0.004). AA patients more frequently experienced difficult weaning from mechanical ventilation, a higher incidence of postoperative V-A ECMO, more frequent anastomotic complications, and longer ICU stays, as compared to controls. Multivariate analysis identified older age (OR 1.11, 95% CI 1.01–1.25, p-value 0.047) and higher postoperative dobutamine dosage (OR 2.25, 95% CI 1.15–5.01, p-value 0.026) as the only significant predictors of new-onset AA within one month of LT.ConclusionsIn our cohort, the incidence of new-onset AAs was 32% after bilateral LT. AA patients experienced worse short- and mid-term outcomes compared to controls. Furthermore, this study highlights older age and postoperative dobutamine administration as significant predictors of new-onset AA following bilateral LT. Further research is needed to clarify the causal relationships and long-term implications of AA on the clinical course of LT recipients.